Evaluation of External Monitoring of Drinking Water in PDAM Tirta Benteng and Tirta Kerta Raharja, Tangerang City - Hanung Nurany; Eko Handoyo; Ira Ayu Hastiaty; Muhammad Fadli Ramadhansyah (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The government and water supply companies, such as Regional Drinking Water Company (PDAM), have the responsibility to ensure the availability of safe and quality drinking water. Regular external monitoring is necessary to ensure that the drinking water provided by PDAM meets established health and safety standards. PDAM Tirta Benteng and PDAM Tirta Kerta Raharja operates in Tangerang City, is responsible for providing safe and quality drinking water to the community. This research went through the stages of sampling, testing the quality of drinking water samples, and analysis using descriptive statistical methods. The evaluation covers aspects such as sampling methods, frequency of testing, and laboratory analyses used. The study also explores the impact of the evaluation results on improving drinking water quality and the improvement measures that can be implemented. This is important not only to ensure that the public gets safe drinking water but also to support transparency and accountability in the provision of drinking water services by public institutions. The comprehensive evaluation is hoped to provide a valuable contribution to efforts to monitor and improve the quality of drinking water in Tangerang City and serve as a basis for developing more effective policies in safeguarding public health through the provision of safe and quality drinking water.